Analisis Pola Kinerja BUMDES Dalam Upaya Peningkatan Pendapatan Asli Desa - Evianti, Elsa; Irawan, Dwi; Ayu Amalia, Firda; Wahyuning Astuti, Sri Wibawani (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2024)
Village original income can be said to be a benchmark for whether a village is developing or not. A routine source that comes from Village Original Income is the existence of BUMDes which can increase village original income which makes villages able to optimize the village economy. This research aims to determine the performance pattern of BUMDes in helping to increase village original income. Performance patterns can be linked to the roles and strategies carried out. Data collection methods use observation, interview and documentation techniques. The observation technique is carried out by direct observation by researchers who go to the field. The role of BUMDes in increasing PAD is from BUMDes unit businesses that are already running. With the development of business units, the good performance pattern of BUMDes is proven by the Village Original Income increasing every year. The active performance of BUMDes can help the village economy or the village community itself so that the village economy and community become stable and of course can improve the welfare of various village parties. The difference in this research lies in the BUMDes units in the village, namely examining aspects of the role of BUMDes, aspects of BUMDes strategy and aspects of BUMDes performance patterns which were not studied by previous research.